The "Hidden" Reductive [2+2+1]‐Cycloaddition Chemistry of 2‐Phosphaethynolate Revealed by Reduction of a Th‐OCP Linkage. (22nd December 2020) - Du, Jingzhen; Balázs, Gábor; Wooles, Ashley J.; Scheer, Manfred; Liddle, Stephen T.
Abstract: The reduction chemistry of the newly emerging 2‐phosphaethynolate (OCP) − is not well explored, and many unanswered questions remain about this ligand in this context. We report that reduction of [Th(Tren TIPS )(OCP)] (2, Tren TIPS =[N(CH2 CH2 NSiPr i 3 )] 3− ), with RbC8 via [2+2+1] cycloaddition, produces an unprecedented hexathorium complex [{Th(Tren TIPS )}6 (μ‐OC2 P3 )2 (μ‐OC2 P3 H)2 Rb4 ] (5 ) featuring four five‐membered [C2 P3 ] phosphorus heterocycles, which can be converted to a rare oxo complex [{Th(Tren TIPS )(μ‐ORb)}2 ] (6 ) and the known cyclometallated complex [Th{N(CH2 CH2 NSiPr i 3 )2 (CH2 CH2 SiPr i 2 CHMeCH2 )}] (4 ) by thermolysis; thereby, providing an unprecedented example of reductive cycloaddition reactivity in the chemistry of 2‐phosphaethynolate. This has permitted us to isolate intermediates that might normally remain unseen. We have debunked an erroneous assumption of a concerted fragmentation process for (OCP) −, rather than cycloaddition products that then decompose with [Th(Tren TIPS )O] − essentially acting as a protecting then leaving group. In contrast, when KC8 or CsC8 were used the phosphinidiide C−H bond activation product [{Th(Tren TIPS )}Th{N(CH2 CH2 NSiPr i 3 )2 [CH2 CH2 SiPr i 2 CH(Me)CH2 C(O)μ‐P]}] (3 ) and the oxo complex [{Th(Tren TIPS )(μ‐OCs)}2 ] (7 ) were isolated. Abstract : A reaction with the overall appearance of (OCP) − concerted cleavage is revealed to proceed through a [2+2+1]‐cycloaddition reaction intermediate, introducing an unprecedented example of (OCP) − cycloaddition under reducing conditions to the established neutral and oxidative cycloaddition classes of (OCP) − reactivity.